Fusion cuisine - Gregos, Katerina; Skamaga, Maria; Isaak, Jo Anna; Martinez, Rosa; Michalopoulou, Amanda; Tillman, Lynne; Deste Foundation for contemporary Art, Athens (Athens : Deste Foundation, 2002)
Antoni, Janine ; von Bonin, Cosima ; Bonvicini, Monica ; Bruguera, Tania ; Bul, Lee ; Chang, Patty ; Dahl, Camilla ; Emin, Tracey ; Fleury, Sylvie ; Hanzlova, Jitka ; Harkness, Hilary ; Jackson, Eliza ; Lou, Liza ; et al.
Deste Foundation, Centre for Contemporary Art, 20 June - 30 October 2002.
kunstcatalogus